Lessons from a Mouse Model Characterizing Features of Vascular Cognitive Impairment with White Matter Changes - Masafumi Ihara; Hidekazu Tomimoto (Journal of Aging Research)
With the demographic shift in age in advanced countries inexorably set to progress in the 21st century, dementia will become one of the most important health problems worldwide. Vascular cognitive impairment is the second most common type of dementia after Alzheimer's disease and is frequently responsible for the cognitive decline of the elderly. It is characterized by cerebrovascular white matter changes; thus, in order to investigate the underlying mechanisms involved in white matter changes, a mouse model of chronic cerebral hypoperfusion has been developed, which involves the narrowing of the bilateral common carotid arteries with newly designed microcoils. The purpose of this paper is to provide a comprehensive summary of the achievements made with the model that shows good reproducibility of the white matter changes characterized by blood-brain barrier disruption, glial activation, oxidative stress, and oligodendrocyte loss following chronic cerebral hypoperfusion. Detailed characterization of this model may help to decipher the substrates associated with impaired memory and move toward a more integrated therapy of vascular cognitive impairment.